Formal milk processing sector in Assam: Lessons to be learnt from institutional failure - Sirohi, S.; Kumar, Anjani; Staal, Steven J. (2009)
Assam initiated organised development of milk processing way back in the mid 1960s. The total installed capacity of pasteurisation and chilling plants in the State is 159 thousand and 28.5 thousand litres per day, respectively. The current scenario of the formal milk processing segment in the state is however, grim. The created infrastructure is either largely defunct or grossly under-utilized. The functional plants are operating at very low level of their installed capacity, have limited product profile, high returns of marketed milk, substantial handling and curdling losses, low productivity of capital and labour and huge operational losses. The poor performance of the plants has been attributed to the establishment of milk processing units without an appropriate assessment of output demand and input supply and ascertainment of economic viability of the plants. In addition, the supporting institutional and infrastructural mechanism has not been put in place and a systematic business and management plan to run the system has not been formulated. Drawing lessons from the institutional failure, the study has suggested some possible interventions and policy initiatives for strengthening the dairy processing activities in the state of Assam.